Exploring age-related changes in saccades during cognitive tasks in healthy adults - Yang, Hee Won; Choe, Jin Yeong; Noh, Soo Rim; Kim, Jeong Lan; Han, Ji Won; Kim, Ki Woong (Frontiers in Behavioral Neuroscience, 2024)
Introduction Although eye movements such as saccades are related to internal cognitive processes and are independent of visual processing, few studies have investigated whether non-visual cognitive tasks simultaneously affect horizontal and vertical saccades in younger and older adults. Methods We recruited 28 younger adults aged 20–29 years and 26 older adults aged >60 years through advertisements in community settings. All participants were free of major psychiatric, neurological, or ocular diseases. All participants performed the mental arithmetic task (MAT) and verbal fluency task (VFT). The primary measures were saccade parameters, including frequency, mean amplitude, and mean velocity. Results During MAT and VFT, the frequencies of horizontal and vertical saccades increased (p = 0.0005 for horizontal saccade in MAT; p < 0.0001 for horizontal saccade in VFT; p = 0.012 for vertical saccade in MAT; p = 0.001 for vertical saccade in VFT), but were comparable between MAT and VFT. The old group showed a slower vertical saccade than the young group during the tasks (p = 0.011 in the MAT phase; p = 0.006 in the VFT phase). The amplitude of the horizontal saccade decreased in both groups during MAT compared to the resting period (p = 0.013), but did not change significantly during VFT. Discussion Saccade parameters can change during non-visual cognitive tasks with differences between age groups and saccade directions. This study significantly contributes to our understanding of the distinct dynamics of horizontal and vertical saccades across various age group in cognitive aging, despite its restricted focus on specific saccade parameters and cognitive tasks, and inclusion solely of cognitively normal individuals. This study highlights the importance of saccade analysis in elucidating age-related cognitive changes. In conclusion, saccades should be examined in future studies as a potential non-invasive biomarker for early detection of cognitive decline and neurodegenerative diseases.